VIS-NIR spectral reflectance for discretization of soils with high sand content - Pereira, Gustavo Eduardo; Sequinatto, Letícia; Almeida, Jaime Antonio de; ten Caten, Alexandre; Mota, Josie Moraes (Semina: Ciências Agrárias, 2019)
The aim of this study is to evaluate the spatial distribution and relationships between the physicochemical attributes and radiometry of soils with high sand contents. One hundred surface horizon samples were collected for physicochemical and spectral analyses of the soil. The samples were selected spatially by the conditioned Latin hypercube method. The physicochemical analyses consisted of granulometry, organic carbon content, and iron oxides content, extracted using sodium dithionite-citrate-bicarbonate (DCB). The spectral response of the soils was analyzed in the 400 to 1000 nm range. The spectral curves were obtained from the samples of the surface horizons, which were categorized according to the attribute in question. The relationship between the soil physicochemical attributes and soil radiometry was evaluated through a Pearson's correlation. There was a tendency for the organic carbon content to decrease with an increase in soil depth, associated with the presence of soils with higher sand contents. For soils with iron contents lower than 80 g kg-1, there was an increase in the reflectance along the spectrum, whereas for soils with contents between 80 and 160 g kg-1, the reflectance decreased after 600 nm, with greater variation along the spectrum for soils with iron contents higher than 120 g kg-1. The diffuse reflectance spectroscopy could potentially allow for granulometric distinction between the soils evaluated.